Tengku Tan Sri Dr Mahaleel inaugurates UMP’s National Public Lecture - UMP, PNC
Universiti Malaysia Pahang (UMP) was thrilled when an admirable national corporate figure, Tan Sri Dr. Tengku Mahaleel Tengku Ariff, was gracious to inaugurate the National Public Lecture – held for the first time at the university.